The Spatial Pattern of Poverty and It's Alleviation Strategy through The Village Fund Policy - Sutresno Sutresno; Ernan Rustiadi; Galuh Syahbana Indraprahasta (International Journal of Economics Development Research (IJEDR), 2023)
The aims of this study are: (1) To analyze the spatial distribution of Poverty in Brebes Regency in 2021. (2) To analyze the effect of implementing village funds and other factors (MSMEs) on the poverty rate in Brebes Regency from a spatial aspect in 2021. Locations in This research located in Brebes Regency, Central Java Province. The number of villages observed was 298 villages. This research is a quantitate research using secondary data. The methods used to achieve the objectives of this study are: (1) Moran and LISA analysis (Moran Index and LISA Index) to analyze the spatial pattern of Poverty; (2) weighted spatial regression analysis (GWR) to determine the effect of variables thought to influence Poverty. The results of this research indicated by the Moran Index value of 0.509409 which indicates a positive autocorrelation or clustering (cluster). This value indicates that adjacent villages have relatively the same characteristics. The Lisa test illustrates the spatial pattern of Poverty that is clustered into four poverty criteria, namely 40 villages with high-high criteria, 69 villages with low-low criteria. A total of 6 villages are low-high and 3 are high-low criteria. Based on the results of the GWR analysis, it was also found that all the variables tested, namely spending on village funds and the number of MSMEs in each village, reduced in reducing Pove significantly reduced several villages.